NITRATE CONTENT OF THE EDIBLE PARTS OF VEGETABLES AND SPICE PLANTS - Joanna Majkowska-Gadomska; Katarzyna Arcichowska; Brygida Wierzbicka (Acta Scientiarum Polonorum: Hortorum Cultus, 2009)
The objective of a study conducted in the years 2007–2008 was to determine the nitrate content of the edible parts of vegetables and spice plants. The analyzed materials consisted of the following species: tomatoes, carrots, sweet basil and marjoram grown in the field, and tomatoes and chili peppers grown in a plastic tunnel. The experiment comprised different cultivation methods, sowing and planting dates, and fertilization levels. Among the analyzed cultivars of field-grown tomatoes, increased nitrate concentrations were observed in the fruits of cv. Złoty Ożarowski. Similar results were noted when eight tomato cultivars were grown in an unheated plastic tunnel. The fruits of cv. Bawole Serce had the lowest nitrate content, compared with the remaining tomato cultivars. Supplemental fertilization of tomato plants grown under cover significantly contributed to nitrate accumulation. The fruits of chili peppers grown in a plastic tunnel had a very low nitrate content. As regards marjoram, the highest nitrate concentrations were reported for the second date of sowing. The average nitrate content of carrot storage roots did not exceed the maximum permissible levels. Supplemental fertilization contributed to an insignificant increase in the N-NO3 content of carrot roots.